João Allen: Collecting the World: An Exhibition and Case Study of the First Private Museum in Portugal. Issue 3 (September 2020) - Castro, Laura
João Allen (1781–1848) was a business man who collected antiques, curiosities, natural history, numismatics, archeological pieces, and fine arts. A trip to Italy in 1826–1827 was fundamental to his collection building, to the opening of the first private museum in Portugal, the Allen Museum in Porto (1837), and to the identity of one of Portugal's most important museums, the Museu Nacional de Soares dos Reis created in 1833 under a different designation. Allen's Grand Tour of Italy and his eclecticism were the cornerstone of the exhibition that took place in this museum in 2018. This article addresses the way in which the exhibition reflects the museum itself and recalls the formation of collections which are of great importance for the history of European museums due to what they reveal about the political and cultural circumstances of their times. Finally, we point out some possible developments concerning the permanent exhibition of the museum.